2017
DOI: 10.1136/bmjopen-2016-014438
|View full text |Cite
|
Sign up to set email alerts
|

Detection of peripheral and central sensitisation at acupoints in patients with unilateral shoulder pain in Beijing: a cross-sectional matched case–control study

Abstract: ObjectiveTo investigate the pattern of experimental pain responses at acupoints in patients with unilateral shoulder pain.DesignA cross-sectional matched study.SettingAcupuncture and Moxibustion Department, Beijing Hospital of Traditional Chinese Medicine Affiliated to Capital Medical University.ParticipantsVolunteer samples of 60 participants (30 patients with unilateral shoulder pain, 30 healthy controls).InterventionsNot applicable.Main outcome measuresPressure pain thresholds (PPTs) were measured at four a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…Therefore, acupoint sensitization is an important prerequisite that enables it to perceive and respond to outside stimuli, allowing it to contribute to the restoring of body functions weakened by disease. In addition, as disease indicators located on the body surface, sensitized acupoints can be used in clinical prognosis and disease monitoring practices [ 13 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, acupoint sensitization is an important prerequisite that enables it to perceive and respond to outside stimuli, allowing it to contribute to the restoring of body functions weakened by disease. In addition, as disease indicators located on the body surface, sensitized acupoints can be used in clinical prognosis and disease monitoring practices [ 13 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The pressure pain threshold (PPT) is a semiobjective method used to quantify localised pain 22 23. Clinical studies have confirmed that the sensitivity (PPT) at acupoints changes when patients are in a diseased state, such as shoulder pain,24 knee osteoarthritis,25 primary dysmenorrhea26 and premenstrual syndrome 27. The degree of change in the PPT may objectively reflect the intensity of acupoint sensitisation and it may be related to the disease status 28.…”
Section: Introductionmentioning
confidence: 99%
“…Acupoint sensitization significantly affects the receptive field size and the sensitivity of an acupoint and thus enhances its therapeutic function , which includes receiving stimuli and regulating body function. In addition, as a reflection of disease activity on the body surface, a sensitized acupoint can hold high clinical value . Therefore, the structural changes and functional characteristics of microcirculation during acupoint sensitization need to be clarified to improve diagnostic and treatment capabilities, as well as better understand of acupoint connotation.…”
Section: Introductionmentioning
confidence: 99%